Optimization of body balance indices according to Body Mass Index categories during physical education lessons for university students - George D. Mocanu; Gabriel Murariu; Vladimir Potop (IP Iermakov S.S., 2022)
Background and Study Purpose. Body stability is an important factor in the manifestation of human motor skills. The purpose of the research is to evaluate the efficiency of balance exercises, applied for 28 weeks, with a frequency of one activity / week, on a group of undergraduate students of the "Dunărea de Jos" University of Galați. Material and Methods. 195 subjects participated (99 males and 96 females), divided for analysis into 3 groups (underweight, N = 21, age = 20.16 ± .38, BMI = 17.46 ± .20); (normal weight, N = 111, age = 20.30 ± .21, BMI = 21.70 ± .17); (overweight / obese, N = 63, age = 19.90 ± .18, BMI = 30.69 ± .61). The tests were applied at 3 distinct times: initial T1 at the beginning of the academic year, intermediate T2 towards the end of semester 1 and final T3 at the end of semester 2. 3 static balance assessment tests were used (One leg standing test with closed eyes, Stork test and Flamingo test), respectively 4 tests to evaluate the dynamic balance (Bass test, Functional reach test, Walk and turn field sobriety test and Fukuda test). Results. ANOVA with repeated measurements and the differences between the test moments highlight in most cases values ​​of F associated with significant thresholds (p <0.05), so there is an improvement in results for all 3 groups. The differences between T1 and T2 tests are larger than those between T2 and T3, so for almost all tests the progress is higher in the first semester, and in semester 2 there is a slight reduction, as a result of adapting to the proposed exercises. Even if they progress significantly, the group of overweight people has obviously weaker average results than normal weight and underweight people, signaling numerous individual cases that have problems in maintaining static balance and commit errors in dynamic balance tests. The better performances of the underweight in 3 cases (One leg standing test, Flamingo test Fukuda test and Walk and turn field sobriety test) cannot be generalized due to their small number compared to the other 2 groups, and this aspect can be considered as a new direction of investigation. Conclusions. There are premises for a favorable evolution of the balance indices for the group tested in this age group, but it must be taken into account that the low initial fitness level (generated by the lack of concerns for a lifestyle based on physical activities) is a factor that facilitated these less spectacular advances, but still statistically significant.